Amartya Sen e a questão da racionalidade na teoria econômica - Patrick Allan Ferreira Alves (2022)
The work is divided into six chapters, with the two central chapters focusing on the criticisms made by the Indian philosopher and economist Amartya Sen to the prevailing rational action theory of economics, from its two main characterizations: rational action as one that is guided by the internal consistency of choices and rational action as self-interested behavior by the part of the decision maker. Sen's works span from the 1970s to the present days, with the introduction of new concepts and shifts in focus as his ideas about rationality evolved. However, the opposition to the conception of rationality that seeks to assess the consistency of choices without resorting to some external reference as represented by the preferences and objectives of agents, as well as to the persistent negligence in studying of behaviors that seem to go against the perceived well-being of the agents, remained a constant in his work. Some articles and concepts from Sen's work, such as the concept of “commitment”, have become classics in the study of rationality in economic theory, and remain relevant to current discussions about the limits and alternatives to the still predominant theory of rational action. The work also engages with some of Sen's critics about the best methods to address the perceived shortcomings of the conventional approaches.